MHD flow of hybrid nanofluid past a stretching sheet: double stratification and multiple slips effects - Yahaya, Rusya Iryanti; Md Ali, Fadzilah; Arifin, N. M.; Khashi'ie, Najiyah Safwa; Isa, S. S. P. M. (Lviv Polytechnic National University, 2022)
Studies of hybrid nanofluids flowing over various physical geometries and conditions are popular among researchers to understand the behavior of these fluids. Thenceforth, the numerical solutions for hybrid Ag-CuO/H2O nanofluid flow over a stretching sheet with suction, magnetic field, double stratification, and multiple slips effects are analyzed in the present study. Governing equations and boundary conditions are introduced to describe the flow problem. Then, similarity variables are applied to transform the equations into non-linear ordinary differential equations and boundary conditions. The numerical computation for the problem is done in Matlab (bvp4c solver), and the results are presented in tables and graphs. It is found that the rise in solutal slip and stratification parameters reduces the Sherwood number. Meanwhile, the increase in thermal slip and stratification parameters lowers the Nusselt number. The skin friction coefficient is observed to increase with the augmentation of the hydrodynamic slip parameter.